2009
DOI: 10.1002/mus.21140
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of foot and ankle manifestations in children with CMT1A

Abstract: We studied the timing and progression of foot and ankle changes in 81 children with genetically confirmed Charcot-Marie-Tooth disease type 1A (CMT1A) and determined their impact on motor function and walking ability. Foot deformity, weakness, pain, cramps, and instability were a common feature of CMT1A. Foot structure evolved toward pes cavus from early childhood to adolescence, although a subgroup with normal and planus feet remained. Foot strength increased with age, although compared to age-equivalent norms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
119
1
13

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(142 citation statements)
references
References 46 publications
9
119
1
13
Order By: Relevance
“…Previous research has demonstrated that despite an increase in ankle dorsiflexion strength as children with CMT1A age, strength scores move further away from the age-equivalent norms. 6 The relationship between increasing age and calf cramp in CMT1A is supported by previous research identifying a 79% prevalence of lower limb muscle cramp in adults with CMT. 1 Of the markers of CMT1A progression observed in this study (e.g., foot alignment, ankle contracture, balance, and nerve conduction studies), only hand tremor was significantly correlated with calf cramp.…”
supporting
confidence: 53%
“…Previous research has demonstrated that despite an increase in ankle dorsiflexion strength as children with CMT1A age, strength scores move further away from the age-equivalent norms. 6 The relationship between increasing age and calf cramp in CMT1A is supported by previous research identifying a 79% prevalence of lower limb muscle cramp in adults with CMT. 1 Of the markers of CMT1A progression observed in this study (e.g., foot alignment, ankle contracture, balance, and nerve conduction studies), only hand tremor was significantly correlated with calf cramp.…”
supporting
confidence: 53%
“…25 The GAITRite is a 420cm length mat, which has 16 128 sensors at a resolution of 1/cm 2 and a sample rate of 80 Hz. The reliability and validity of the GAITRite has been well established in children.…”
Section: Procedures and Materialsmentioning
confidence: 99%
“…Özellikle aşil tendonunda oluşan kontraktürler de bu kompansatuar postürün sonucunda sekonder problemler olarak gelişirler (24,25). Charcot-Marie-Tooth'da ise ayak ve ayak bileği kuvvetinde seçici zayıflık ve imbalansa bağlı limitli bir ayak bileği -ya da ayak bileği ekini-bu hastalığa sahip çocuk ve yetişkinlerde görülen ortak bir bozukluktur (8).…”
Section: Discussionunclassified
“…Bu kısalıklar DMD ve CMT'de kas zayıflığı ve denge bozukluğunun karakteristik paternlerine bağlı olarak vücut ağırlık merkezindeki değişimlerin ve süregelen postüral kompansasyonların sonucu olarak meydana gelmektedir (5,6). Bu durum hastaların mobilite ve dengelerini limitlerken, sağlıkla ilgili yaşam kalitelerinde de azalmaya sebep olur (3,7,8).…”
Section: Introductionunclassified